A study of clinical and biochemical correlation in patients of psoriasis in acute exacerbation - Neerja Puri; B B Mahajan (Our Dermatology Online, 2014)
Introduction: Psoriasis is a genetically determined chronic disease of skin in which a number of biochemical alterations take place during its course. The main objectives of our study were to calculate various biochemical parameters in psoriasis correlate them clinically. Materials and Methods: An attempt was made to detect the biochemical changes during its exacerbations. Fifty biopsy proved psoriasis patients were selected. Clinical examination and the various biochemical tests were performed at the time of enrollment and at the end of eight weeks of treatment. Results: Hyperurecemia was seen in 16% patients and hypocalcemia was seen in 10 % patients and hypoalbuminaemia was seen in 56% patients. Conclusion: With improvement of clinical picture, a shift of biochemical values towards normal was recorded.